Utilization of Systemic Chemotherapy in Advanced Urothelial Cancer: A Retrospective Collaborative Study by the Hellenic Genitourinary Cancer Group (HGUCG) - Bamias, A.; Peroukidis, S.; Stamatopoulou, S.; Tzannis, K.; Koutsoukos, K.; Andreadis, C.; Bozionelou, V.; Pistalmatzian, N.; Papatsoris, A.; Stravodimos, K.; Varthalitis, I.; Karamouzis, M.; et al. (Clinical Genitourinary Cancer, 2016)
Background Advanced urothelial cancer (AUCa) is associated with poor long-term survival. Two major concerns are related to nonexposure to cisplatin-based chemotherapy and poor outcome after relapse. Our purpose was to record patterns of practice in AUCa in Greece, focusing on first-line treatment and management of relapsed disease. Methods Patients with AUCa treated from 2011 to 2013 were included in the analysis. Fitness for cisplatin was assessed by recently established criteria. Results Of 327 patients treated with first-line chemotherapy, 179 (55%) did not receive cisplatin. Criteria for unfitness for cisplatin were: Eastern Cooperative Oncology Group (ECOG) performance status (PS) ≥ 2, 21%; creatinine clearance ≤ 60 mL/min, 55%; hearing impairment, 8%; neuropathy, 1%; and cardiac failure, 5%. Forty-six patients (27%) did not fulfill any criterion for unfitness for cisplatin. The main reasons for these deviations were comorbidities (28%) and advanced age (32%). Seventy-four (68%) of 109 patients who experienced a relapse received second-line chemotherapy. The most frequent reason for not offering second-line chemotherapy was poor PS or limited life expectancy (66%). Conclusion In line with international data, approximately 50% of Greek patients with AUCa do not receive cisplatin-based chemotherapy, although 27% of them were suitable for such treatment. In addition, about one third of patients with relapse did not receive second-line chemotherapy because of poor PS or short life expectancy. Enforcing criteria for fitness for cisplatin and earlier diagnosis of relapse represent 2 targets for improvement in current treatment practice for AUCa. © 2016 Elsevier Inc.
Keywords: Advanced urothelial cancer; Fitness for cisplatin; Patterns of practice